Attribution Analysis of Discharge Variations in the Inner Mongolia Basin of the Yellow River - Guo, Yongxiao (International Journal of Natural Resources and Environmental Studies, 2024)
Climate change and human activities are the main causes of discharge variation. Therefore, calculating the contribution of climate change and human activities to discharge variation in the Inner Mongolia Basin of the Yellow River can provide a reference basis for alleviating water resources stress in the Inner Mongolia Basin of the Yellow River. Firstly, based on the water balance theory and the Budyko hypothesis-based evapotranspiration formula, this study constructed a coupled water and heat balance equation and calibrated and validated the model using observed annual discharge depth data from the Toudao Guai hydrological station. The results show that the water-heat coupling model has good simulation accuracy at the annual scale, with NSE=0.76, RMSE=10.45, and RRMSE=19.5%, and overall, the simulated discharge results are close to the observed values. Secondly, this study also used the Mann-Kendall test method to determine the abrupt change points of discharge and analyzed the contribution rates of various meteorological factors. The results indicate that precipitation accounts for 88.79% of the discharge variation in the Inner Mongolia segment of the Yellow River basin, followed by land surface changes at 13.6%, while potential evaporation has the smallest contribution to discharge variation.